2021
DOI: 10.3389/fimmu.2021.651357
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral TIGIT+ T Follicular Helper Cells That Produce High Levels of Interleukin-21 via OX40 Represent Disease Activity in IgG4-Related Disease

Abstract: ObjectivesMultiple studies suggest that interleukin (IL)-21 plays a pivotal role in the differentiation of B cells and activation of cytotoxic T cells and is involved in the pathogenesis of IgG4-related disease (IgG4-RD). T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) is a new marker of T follicular helper (Tfh) cells, yet its significance remains unknown. The objective of this study was to investigate whether TIGIT expression could detect high IL-21-producing peripheral Tfh populations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…However, upon further phenotypic characterization of CD4 + Tcm, we observed significantly elevated ( P = 0.0061) frequencies of TIGIT-expressing CD4 + Tcm day 14 after B1 ( Figure 3A ), the same time point at which SIV + IL-21–treated animals had significantly improved influenza HAI titers compared with SIV + IL-21–untreated animals ( Figure 1E ). Interestingly, pTfh cells expressing TIGIT have recently been shown to exhibit strong B cell help functions and high levels of IL-21 production, and they have been shown to promote differentiation of plasmablasts and IgG production ( 26 , 39 ). Furthermore, we found that there was a trend ( P = 0.0727) of increased TIGIT expression on pTfh cells in IL-21–treated animals ( Figure 3D ), and influenza HAI titers day 14 after B1 correlated with both TIGIT + CD4 + Tcm ( r = 0.6808, P = 0.0120) ( Figure 3B ) and TIGIT + pTfh ( r = 0.7387, P = 0.0112) cells ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…However, upon further phenotypic characterization of CD4 + Tcm, we observed significantly elevated ( P = 0.0061) frequencies of TIGIT-expressing CD4 + Tcm day 14 after B1 ( Figure 3A ), the same time point at which SIV + IL-21–treated animals had significantly improved influenza HAI titers compared with SIV + IL-21–untreated animals ( Figure 1E ). Interestingly, pTfh cells expressing TIGIT have recently been shown to exhibit strong B cell help functions and high levels of IL-21 production, and they have been shown to promote differentiation of plasmablasts and IgG production ( 26 , 39 ). Furthermore, we found that there was a trend ( P = 0.0727) of increased TIGIT expression on pTfh cells in IL-21–treated animals ( Figure 3D ), and influenza HAI titers day 14 after B1 correlated with both TIGIT + CD4 + Tcm ( r = 0.6808, P = 0.0120) ( Figure 3B ) and TIGIT + pTfh ( r = 0.7387, P = 0.0112) cells ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…The specific transcription factor Bcl-6 is selectively expressed in Tfh cells but is highly expressed in CXCR5 hi CCR7 low/-Tfh cells in human and mouse GCs (34)(35)(36)(37). The IL-21 cytokine is highly and specifically secreted by Tfh cells, which promotes the proliferation of Tfh cells and helps B cell differentiation and antibody secretion, which is characteristic of Tfh cells (38)(39)(40)(41)(42). ICOS deficiency significantly reduces GC reactions and Tfh cells in mice and humans, which indicates that ICOS expressed in Tfh cells is essential for the differentiation and maintenance of Tfh cells, GC formation, B cell differentiation and antibody responses (43)(44)(45).…”
Section: The Phenotypes and Functions Of Tfh Cellsmentioning
confidence: 99%
“…T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT), a co-inhibitory receptor discovered recently (84), was thought to be a novel Tfh marker. Akiyama et al (85) analyzed the expression of TIGIT in peripheral CD4 + T cell subsets and found that peripheral Tfh cells have higher expression of TIGIT than Th cells. They also observed that TIGIT + Tfh cells secretes more IL-21 than TIGIT -Tfh cells, which could be used to trace the progression of IgG4-RD.…”
Section: Th17 Cellsmentioning
confidence: 99%
“…Akiyama et al. ( 85 ) analyzed the expression of TIGIT in peripheral CD4 + T cell subsets and found that peripheral Tfh cells have higher expression of TIGIT than Th cells. They also observed that TIGIT + Tfh cells secretes more IL-21 than TIGIT - Tfh cells, which could be used to trace the progression of IgG4-RD.…”
Section: Adaptive Immunitymentioning
confidence: 99%